Microstructure and corrosion behavior of Al-Ti-TiC-CNTs/AZ31 magnesium matrix composites prepared using laser cladding and high speed friction stir processing. (August 2022) - Liu, Fenjun; Li, Aodong; Shen, Zhikang; Chen, Haiyan; Ji, Yan
Highlights: Sound magnesium matrix composites were produced using laser cladding and high speed friction stir processing. High speed friction stir processing has a significant influence on microstructural evolution. Surface microhardness value was significantly enhanced. Excellent corrosion properties were obtained. Abstract: Al-Ti-TiC-CNTs/AZ31 magnesium matrix composites (MMCs) were prepared using laser cladding (LC) and high speed friction stir processing (HS-FSP). The surface microstructure, phase composition, microhardness distribution and corrosion resistance of the MMCs were studied using scanning electron microscope (SEM), X-ray diffraction (XRD), microhardness tester and electrochemical workstation. The composite layers were composed of phases with different geometric morphology and distribution characteristics identified as α-Mg, Al12 Mg17 and TiC phases. A defect-free LC composite layer with refined microstructure and a sound metallurgical bonding interface between the LC composite layer and the matrix were observed. In addition to maintaining the sound metallurgical bonding interface, the microstructure of the LC composite layer was significantly refined and densified after being subjected to HS-FSP. The surface microhardness and self-corrosion potential of the MMCs prepared using LC was obviously enhanced due to the formation of a large number of Al12 Mg17 and TiC phases, but they show a decreasing trend with decreasing the Al12 Mg17 and TiC phases. The MMCs produced using HS-FSP exhibited higher surface microhardness and better corrosion properties than those of the LC due to the formation of finer and denser microstructure and higher numbers of Al12 Mg17 and TiC phases in the composite layers.